ANALYSIS OF DIGITAL CULTURAL BEHAVIOR IN GEN Z STUDENTS OF UINSU COMMUNICATION SCIENCE - Nasution, Miftahul Hasniyah; Mutiara Febriana; Purba, Umi Hasanah (Academic Solution Publisher, 2024)
This journal discusses that digital culture plays a significant role in the daily lives of Generation Z students in the Communication Studies Department at UINSU. The positive experiences of using communication technology include ease of interaction and access to information, but there are also risks such as the spread of misinformation and negative content. It is important to understand the meaning of digital cultural communication through framing theory and a phenomenological approach so that Generation Z can use technology responsibly and intelligently. This study analyzes the digital cultural behavior of Generation Z students in the Communication Studies Department at UINSU. It employs a descriptive qualitative approach using in-depth interviews. The findings indicate that Generation Z students have diverse motives for using digital communication, resulting in both positive and negative experiences. Digital technology enables them to stay connected with others over long distances, yet it also carries risks such as the spread of false information.